Organically-modified magnesium silicate nanocomposites for high-performance heavy metal removal. Issue 100 (12th October 2016) - Yu, Yichang; Hu, Zhangjun; Chen, Zhenyong; Yang, Jiaxiang; Gao, Hongwen; Chen, Zhiwen
Abstract : A disulfide-grafted polyethyleneimine (PES)@Mg2 SiO4 composite was synthesized, characterized, and used successfully to remove heavy metals from wastewater. Abstract : A disulfide-grafted polyethyleneimine (PES)@Mg2 SiO4 composite was synthesized, characterized, and used successfully to remove heavy metals from wastewater. It was grafted with a huge number of dithiocarbamate moieties as sites for specific adsorption. By comparative studies, it was found that the morphology, structure and properties were influenced by the trapped organic components in the composites. PES@Mg2 SiO4 exhibits a larger specific surface area and better adsorption activity compared with Mg2 SiO4, polyethyleneimine (PEI)@Mg2 SiO4 and PEI@Mg2 SiO4 –CS2 . The adsorption behaviors of the obtained composites were investigated for the recovery of Hg 2+, Pb 2+ and Cd 2+ . PES@Mg2 SiO4 shows the highest adsorption capacities of 714 mg g −1 for Hg 2+, 400 mg g −1 for Pb 2+ and 323 mg g −1 for Cd 2+, which fits the Langmuir isotherm model. Besides this, it also exhibits excellent adsorption capacity for Cu 2+, Bi 3+ and metal complexes. Its application in petrochemical wastewater demonstrates its enormous potential for heavy metal wastewater treatment.